2019
DOI: 10.1038/s41438-019-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of lysine succinylation in patchouli plant leaves

Abstract: Lysine succinylation is a novel, naturally occurring posttranslational modification (PTM) in living organisms. Global lysine succinylation identification has been performed at the proteomic level in various species; however, the study of lysine succinylation in plant species is relatively limited. Patchouli plant (P. cablin (Blanco) Benth., Lamiaceae) is a globally important industrial plant and medicinal herb. In the present study, lysine succinylome analysis was carried out in patchouli plants to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…The functional classification and subcellular location distribution of succinylated proteins were compared in three plants (paper mulberry, patchouli [ 45 ] and tea [ 30 ]). The cellular components of the three species are characterized by considerable enrichment in categories related to the cell, membrane, macromolecular complex and organelle membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional classification and subcellular location distribution of succinylated proteins were compared in three plants (paper mulberry, patchouli [ 45 ] and tea [ 30 ]). The cellular components of the three species are characterized by considerable enrichment in categories related to the cell, membrane, macromolecular complex and organelle membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Chloroplasts are the specific energy conversion organelles of plant cells [ 47 , 48 ] and convert light energy into chemical energy to support plant life. Previous studies of lysine succinylation in wheat [ 49 ], patchouli plant leaves [ 45 ], Brachypodium distachyon L. [ 29 ] and tomato [ 31 ] identified various succinylation sites and proteins related to photosynthesis and demonstrated potential functional regulation of photosynthesis-related proteins by succinylation. Thus, protein succinylation may be a conserved form of regulation of photosynthesis in various plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Succinylation alters the electrophoretic mobility and isoionic pH of ovalbumin [ 140 ], inactivates the canonical carnitine palmitoyltransferase (CPTase) activity, decreases the enolase activity [ 141 ], and promotes cell invasion and migration [ 139 ]. Succinylation in plants has been reported in rice [ 34 ], tomato [ 142 ], B. distachyon L. [ 135 ], patchouli [ 143 ], and tea [ 144 ]. However, the effect of lysine succinylation in plants is relatively limited.…”
Section: Starch Biosynthesis-related Proteins Targeted By Ptmsmentioning
confidence: 99%
“…In plants, chloroplast photosynthesis is an important biochemical reaction that converts light energy into chemical energy to maintain plant life [49]. Research on plant defense and photosynthesis has indicated that the rate of photosynthesis is reduced after pathogen invasion, such as in barley infected with powdery mildew, potato infected with Phytophthora infestans, and soybean infected with Phytophthora sojae [50][51][52].…”
Section: Defensive Photosynthetic Activities Of Wheat Stem Bases Undementioning
confidence: 99%